2013
DOI: 10.1007/s00268-013-2265-5
|View full text |Cite
|
Sign up to set email alerts
|

Open Versus Thoracoscopic Esophagectomy in Patients with Esophageal Squamous Cell Carcinoma

Abstract: The perioperative benefit of thoracoscopic esophagectomy included fewer postoperative complications and shorter ICU stays. Mid-term OS and DFS associated with thoracoscopic techniques are at least equivalent to those associated with open procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 42 publications
(60 reference statements)
3
35
0
1
Order By: Relevance
“…The development of complications after esophagectomy leads to increased postoperative morbidity and mortality, a prolonged hospital stay, and additional medical costs. A previous study has reported that minimally invasive esophagectomy and avoiding thoracotomy and laparotomy can reduce the rate of respiratory complications [23]. Other authors suggested that perioperative steroid therapy was effective in inhibiting the release of inflammatory mediators and decreasing the rate of postoperative respiratory complications after esophageal cancer surgery [24].…”
Section: Discussionmentioning
confidence: 99%
“…The development of complications after esophagectomy leads to increased postoperative morbidity and mortality, a prolonged hospital stay, and additional medical costs. A previous study has reported that minimally invasive esophagectomy and avoiding thoracotomy and laparotomy can reduce the rate of respiratory complications [23]. Other authors suggested that perioperative steroid therapy was effective in inhibiting the release of inflammatory mediators and decreasing the rate of postoperative respiratory complications after esophageal cancer surgery [24].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, their study demonstrated uncertainty of MIE in treating advanced pT3 esophageal carcinoma. Hsu et al (21) reported that the 3-year DFS rate was better in the MIE group when treating esophageal squamous cell carcinoma (P=0.007). However, after subgroup analysis, there was no significant difference between MIE and open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Since patients with cervical ESCC would be treated with definitive chemoradiation, only patients with intrathoracic ESCC were included. Preoperative staging workup were previously described [8]. In particular, endoscopic ultrasound (EUS) was an optional procedure, but was required for confirmation of cT1 or cT2 lesions.…”
Section: Methodsmentioning
confidence: 99%
“…The surgical approaches used were minimally invasive esophagectomy (MIE, right-sided video-assisted thoracoscopic surgery [VATS] plus laparoscopic surgery) and hybrid esophagectomy (right-sided VATS plus laparotomy). The details of surgical procedures were previously described [8]. Pathological examination that was conducted according to the 7 th edition AJCC TNM staging system [9].…”
Section: Methodsmentioning
confidence: 99%